Inflectional and Derivational Morphemes in Kim Namjoon’s Speech for Youth Self-Love - Ni Ketut Budiani (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
Morphology plays an important role in understanding how words are formed and how meaning changes through the use of morphemes. This study aims to identify the inflectional and derivational morphemes found in Kim Namjoon’s speech at the United Nations and to analyze their grammatical functions within the context of the speech. Using a descriptive qualitative approach, the researcher analyzed the speech transcript retrieved from UNICEF’s official website. This research relied on documentation for data collection and employed Plag’s (2003) morphological theory in the analysis process. The findings revealed that inflectional morphemes such as -s, -ed, and -ing were used to indicate number, tense, aspect, and person, ensuring grammatical accuracy and sentence clarity. Meanwhile, derivational morphemes such as -er, -ion, -ist, -able, and -ly were used to form new words and change grammatical categories, allowing the speaker to describe roles, ideas, and characteristics more precisely. Overall, the study concludes that both inflectional and derivational morphemes contribute significantly to the structure, clarity, and grammatical coherence of the speech, highlighting the importance of morphology in effective spoken language use.